Visual arts marketing in East Asia. (17th September 2018) - Chang, Yu-Chien; Preece, Chloe
Abstract : Purpose: The purpose of this paper is threefold. First, it reviews the background to, and development of the special issue call for papers on the topic of "Visual arts marketing in East Asia"; second, it introduces the four papers and commentary in the issue; and third, it considers some of the key areas with a rich potential for future directions of research. Design/methodology/approach: The papers in this special issue comprise of both qualitative (e.g. interviews, observation, case studies) and quantitative (surveys) as well as conceptual issues for policy and artists. Moreover, the articles are interdisciplinary, drawing from art history, cultural studies, philosophy and international relations as well as marketing. Findings: Findings and insights relate to topics such as the structure of the visual arts markets of East Asia, political influences on these arts markets, alternative spaces such as art festivals, ambiance and audience experience in museums and new media initiatives. Research limitations/implications: The authors believe that all of the papers have implications for future thinking, research, scholarship and practice in the area of arts marketing, particularly for scholars, cultural institutions and artists working in Asia. Originality/value: As far as the editors are aware, this is the first ever journal special issue on arts marketing in East Asia. In particular, the authors offer some new ideas in thinking about visual arts marketing in Asia as part of this editorial essay, particularly in considering the difficulties for both artists, arts organisations and academics in creating from the "periphery".